The blue hour [videorecording (DVD)] - Boonyawatana, Anucha; Boonyawatana, Anucha; Autta, Anuphap; Upanigkit, Chonlasit; Poonsawas, Attjaphan (Strand Releasing Home Video, 2016)
The blue hour is a sexy supernatural love story about a bullied loner, Tam, who finds solace in the arms of Phum, a boy he meets at a haunted swimming pool. Phum reveals that his family's land has been stolen and the newfound lovers imagine a perfect life together on the disputed land. Haunted by a ghostly presence, Tam struggles to stay connected to reality.